Design of HSIPMM based on multi‐physics fields. Issue 8 (9th May 2018) - Zhang, Fengge; Dai, Rui; Liu, Guangwei; Cui, Tianhao
Abstract : High‐speed permanent magnet motors (HSPMM) have attracted much attention due to the inherent characteristics such as high‐power density, small size, small inertia, and high response. HSPMM is a comprehensive and complex system of multidisciplinary cross‐coupling such as electromagnetism, structural mechanics, rotor dynamic, fluid mechanics and heat transfer. Therefore, the design of HSPMM requires a multidisciplinary and integrated design approach. In this study, a 20 kW, 20, 000 rpm HS interior PMM (HSIPMM) is designed based on multi‐physics fields. To reduce the end length of winding, the back round winding type is adopted, compared with the common structure, it is found that the temperature rise of the stator used back round winding type can be reduced by 11.5%. Finally, the superiority of the proposed HSIPMM is proved by the experimental results, and the efficiency of the motor is about 96.1%.